Duct ligation/de-ligation model: exploring mechanisms for salivary gland injury and regeneration - Wang, Bin; Li, Zhilin; An, Wei; Fan, Gaiping; Li, Dezhi; Qin, Lizheng (Frontiers in Cell and Developmental Biology, 2024)
Sialadenitis and sialadenitis-induced sialopathy are typically caused by obstruction of the salivary gland ducts. Atrophy of the salivary glands in experimental animals caused by duct ligation exhibits a histopathology similar to that of salivary gland sialadenitis. Therefore, a variety of duct ligation/de-ligation models have been commonly employed to study salivary gland injury and regeneration. Duct ligation is mainly characterised by apoptosis and activation of different signaling pathways in parenchymal cells, which eventually leads to gland atrophy and progressive dysfunction. By contrast, duct de-ligation can initiate the recovery of gland structure and function by regenerating the secretory tissue. This review summarizes the animal duct ligation/de-ligation models that have been used for the examination of pathological fundamentals in salivary disorders, in order to unravel the pathological changes and underlying mechanisms involved in salivary gland injury and regeneration. These experimental models have contributed to developing effective and curative strategies for gland dysfunction and providing plausible solutions for overcoming salivary disorders.